Cuidados paliativos à criança com doença crônica: um estudo com enfermeiras assistenciais à luz da teoria do cuidado humano - Silva, Eliane Cristina da (2017)
Introduction: Within pediatric palliative care, nursing care should be provided in a comprehensive way, for both, strategies that favor a quality of life and well-being of the child with chronic illness and his family. Objective: To find out the guidelines used for nurses assistants for the promotion of healthcare aimed at children with chronic disease, in the light of Human Caring Theory. Methodology: Exploratory study with a qualitative approach. The research scenario for two reference hospitals in pediatrics in the state of Paraíba. The study was approved by the Research Ethics Committee of the HULW under protocol nº 1,268,255 and CAAE nº 48333415.3.0000.5183. Data collection took place between October 2015 and January 2016 through a semi-structured interview. The empirical material was analyzed by the Categorical Content analysis technique. Results: Through bibliometric indicators it was possible to see a growing dissemination of studies on the Human Caring Theory, which were predominant and the articles published in national journals between the years 2010 and 2011. The categorization of the data showed that goodness loving care in nurse care actions as well as health and health care are designed for participants as important to the promotion of palliative health care for the child with chronic illness and that the satisfaction that nurses feel when providing care works as a motivating factor for the quality of nursing care. Conclusion: As nurses have demonstrated that they consider the importance of palliative care for children with chronic illness, mainly in relation to their subjective principles and therefore they use care strategies based on loving kindness, not spiritual care and faith. This study opens new horizons on pediatric palliative care and demonstrates a feasibility of the adoption of the Human Caring Theory in nurses' practice of care.